Defending the majesty of Islam Indonesia's Front Pembela Islam, 1998-2003 - Jahroni, Jajang (Islam in Southeast Asia: views from within, 2008)
Indonesia's 1998 reformation movement spawned numerous organizations aimed at either establishing an Islamic state or applying Islamic law. This book focuses on one such movement, Front Pembela Islam (FPI). The study presents the biography of Habib Muhammad Rizieq Syihab, one of FPI's founding fathers and its current head, and discusses the group's creation, activities, and ideology. Finally, it analyzes FPI's organizational bases, recruitment practices, and training methods, including the use of religious teachings to justify the deliberate destruction of entertainment venues where gambling, prostitution, and drinking occur - activities which are seen as corrupting according to Islamic teaching. Jajang Jahroni is a lecturer at the Faculty of Literature and Humanities at Syarif Hidayatullah State Islamic University in Jakarta and a researcher at the Center for the Study of Islamic Society.